Selective excitation of hydrogen doubles the yield and improves the robustness of parahydrogen-induced polarization of low-γ nuclei. Issue 47 (30th November 2021) - Schmidt, Andreas B.; Brahms, Arne; Ellermann, Frowin; Knecht, Stephan; Berner, Stephan; Hennig, Jürgen; von Elverfeldt, Dominik; Herges, Rainer; Hövener, Jan-Bernd; Pravdivtsev, Andrey N.
Abstract : We describe a new method for pulsed spin order transfer of parahydrogen-induced polarization (PHIP) that enables high polarization in incompletely 2 H-labeled molecules by exciting only the desired protons in a frequency-selective manner. Abstract : We describe a new method for pulsed spin order transfer of parahydrogen-induced polarization (PHIP) that enables high polarization in incompletely 2 H-labeled molecules by exciting only the desired protons in a frequency-selective manner. This way, the effect of selected J -couplings is suspended. Experimentally 1.25% 13 C polarization were obtained for 1- 13 C-ethyl pyruvate and 50% pH2 at 9.4 Tesla.